Public Perception in Evaluating Indonesia’s School Zoning Admission Policy: Insight Into the Ongoing Debate - Muhamad Nur Chozin; Lutfiana Wahyu Savitri; Ridwan Eko Apriyanto; Marzuki Marzuki (AL-ISHLAH: Jurnal Pendidikan, 2025)
The New Student Admission (NSA) policy in Indonesia, particularly the zone-based scheme, has sparked public debate. This study examines public perceptions of the policy, identifying key factors influencing acceptance and rejection. A sequential explanatory mixed-method approach was employed, combining quantitative and qualitative data collection. A survey was conducted among 102 parents across 13 provinces in Indonesia from September to October 2023. Findings reveal diverse public opinions on the NSA policy. Opposition stems from concerns about cheating, limited school availability, declining student motivation, and systemic issues. Conversely, supporters highlight the policy’s role in promoting equitable access to education and reducing social class bias. Public sentiment towards policy sustainability is categorized into three groups: those advocating for complete abolition, those favoring improvements, and those supporting full implementation. The persistence of debates suggests the need for policy refinement to address public concerns. The study emphasizes that policy acceptance is closely tied to its perceived effectiveness in ensuring fairness and accessibility. To enhance public acceptance, the study recommends increasing school availability, adapting zoning systems to demographic conditions, intensifying public outreach, and strengthening law enforcement. These measures can improve policy effectiveness and reduce opposition, fostering a more inclusive education system in Indonesia.